2015
DOI: 10.1038/gim.2014.157
|View full text |Cite
|
Sign up to set email alerts
|

Consanguinity and rare mutations outside of MCCC genes underlie nonspecific phenotypes of MCCD

Abstract: Purpose3-Methylcrotonyl-CoA carboxylase deficiency (MCCD) is an autosomal recessive disorder of leucine catabolism that has a highly variable clinical phenotype, ranging from acute metabolic acidosis to nonspecific symptoms such as developmental delay, failure to thrive, hemiparesis, muscular hypotonia, and multiple sclerosis. Implementation of newborn screening for MCCD has resulted in broadening the range of phenotypic expression to include asymptomatic adults. The purpose of this study was to identify facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…8 Shepard et al studied children with Specific symptoms of leucine toxicity such as hypoglycemia, acidosis and others and children with non-specific symptoms such as intellectual disability or seizures. 9 The study found that cases with non-specific symptoms were more likely to have increased regions of homozygosity and that likely explained the patient's symptoms. The possibility remains that 3-MCC deficiency might constitute a predisposition to developmental disabilities in the presence of other stressors.…”
Section: Discussionmentioning
confidence: 89%
“…8 Shepard et al studied children with Specific symptoms of leucine toxicity such as hypoglycemia, acidosis and others and children with non-specific symptoms such as intellectual disability or seizures. 9 The study found that cases with non-specific symptoms were more likely to have increased regions of homozygosity and that likely explained the patient's symptoms. The possibility remains that 3-MCC deficiency might constitute a predisposition to developmental disabilities in the presence of other stressors.…”
Section: Discussionmentioning
confidence: 89%
“…However, the contribution of the GNB5 variant to proband’s ID was complicated by the presence of 3-MCC deficiency, also previously thought to cause mild ID [ 58 , 59 ]. Recent literature on 3-MCC deficiency suggests very low disease penetrance and propose that the neurological symptoms may be unrelated to the disorder [ 36 , 60 ]. Hence, the severe ID in the proband is most consistent with GNB5 -related disorder; however, further investigation is required to examine for any interactions between the two molecular diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Reported outcome concerns have included fasting abnormalities, failure to thrive and other problems [2,15]. Shepard et al [22] proposed a difference between symptoms suggestive of leucine toxicity such as hypoglycemia, acidosis and others, and “non-specific” symptoms such as intellectual disability or seizures. That study found that cases with “non-specific” symptoms were more likely to have increased regions of homozygosity, and 5/10 “non-specific” symptom cases studied by exome sequencing had another gene identified that likely explained the patient's symptoms.…”
Section: Discussionmentioning
confidence: 99%